A procedure for synthesizing a specified sidelobe topography using an arbitrary array - Nagesh, S.R.; Vedavathy, T.S. (IEEE transactions on antennas and propagation, 1995)
A simple method to arrive at an optimum set of array excitations to achieve a specified radiation pattern is presented. An auxiliary function is formulated, based on the envelope of the required sidelobe structure and the array factor, in the sidelobe region. This function is minimized, subject to the main lobe constraints and the null steering constraints, to determine the excitations. An iterative procedure is used to generate the desired pattern, with the additional constraints like sidelobe level, symmetric excitation, and so on. The method has been successfully applied to synthesize linear arrays and circular arc arrays and to generate symmetric as well as asymmetric patterns.< >